2011
DOI: 10.2147/opth.s23143
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral intraocular pressure measured by a rebound tonometer

Abstract: Purpose:We investigated at which corneal region the intraocular pressure as measured by the Icare® rebound tonometer (Finland Oy, Espoo, Finland) (hereinafter referred to as IC) was closest to the intraocular pressure as measured by the Goldmann applanation tonometer (hereinafter referred to as GT). We also investigated which parameters would be best for preparing the most suitable model for predicting GT.Methods:A total of 102 normal eyes in 102 subjects were enrolled. IC measurements were carried out at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Decentered iCare measurements have been shown to underestimate measurements correctly taken at the central cornea; in particular, measurements at the inferior cornea showed the poorest correlation with intraocular pressure measured with applanation tonometry. 43 , 44 Difficulty centering the instrument on the cornea was also reflected in the patient feedback obtained in this study. Further improvements to the iCare HOME instrument design may help to reduce the variability of intraocular pressure measurements obtained.…”
Section: Discussionmentioning
confidence: 78%
“…Decentered iCare measurements have been shown to underestimate measurements correctly taken at the central cornea; in particular, measurements at the inferior cornea showed the poorest correlation with intraocular pressure measured with applanation tonometry. 43 , 44 Difficulty centering the instrument on the cornea was also reflected in the patient feedback obtained in this study. Further improvements to the iCare HOME instrument design may help to reduce the variability of intraocular pressure measurements obtained.…”
Section: Discussionmentioning
confidence: 78%
“…It is not known how this may have affected unsupervised measurements performed at home. Decentered iCare measurements have been shown to underestimate pressure when compared to measurements correctly taken at the central cornea; in particular, measurements taken at the inferior cornea showed the poorest correlation with IOP measured with applanation tonometry [ 18 , 19 ]. Datasia et al reported that glaucoma patients were less likely than healthy subjects to have home measurement devices available [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to elucidate these putative erroneous errors; however, to date, these studies have generally neglected to examine the central 4 mm corneal zone within which most readings would normally be acquired, clinically. Instead, studies have measured IOP at positions 2 mm from the limbus [68]. Further, the exact methods adopted to adjust probe position in relation to the cornea are often an approximation using rudimentary techniques [9, 10] and they generally lack any real quantifiable level of precision and accuracy [11].…”
Section: Introductionmentioning
confidence: 99%